Workshops for approaching suicidal behavior: implementation in Primary Health Care - Daniele Cristina Ribeiro dos Santos; Rúbia Aguiar Alencar; Thiago da Silva Domingos
ABSTRACT Objective: to describe the implementation of workshops on the approach of people in psychological distress with suicidal behavior for Primary Health Care workers and managers. Methods: this is an action research developed for Primary Health Care professionals in a city in the countryside of São Paulo. Charles Maguerez's Arch methodology was used as a theoretical framework to construct the workshops. Results: through active strategies and the exercise of reflection-action, the workshops enabled participants to raise awareness on the topic, articulation between professionals and managers, and the co-responsibility required to care for users with suicidal behavior assisted in Primary Health Care. Final considerations: the workshops broadened knowledge, facilitating skill development to qualify Primary Health Care professionals in caring for people with suicidal behavior.